2014
DOI: 10.1016/j.colcom.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Anisotropic Wettability Using Micro-pillar Geometry

Abstract: a b s t r a c tAnisotropic surfaces have great potential in important applications like microfluidic devices, lab-on-chip systems, micro-reactors, coatings and printings. Anisotropic wetting behavior on micro-pillars is of particular interest since micro-scale morphology on many natural anisotropic wetting surfaces are pillar-like structures. It is found that the micro-pillars show anisotropic wettability at Wenzel state and isotropic wettability at Cassie state. Increasing the micro-pillar height will lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…Substantial anisotropic wetting has been observed for 1D micropatterned and nanopatterned , surfaces. Such anisotropy has also been reported in 2D patterned surfaces with micropillar geometry . They have shown that the anisotropy can be controlled by the height of the pillars and is only observed for hydrophilic surfaces.…”
Section: Introductionsupporting
confidence: 61%
“…Substantial anisotropic wetting has been observed for 1D micropatterned and nanopatterned , surfaces. Such anisotropy has also been reported in 2D patterned surfaces with micropillar geometry . They have shown that the anisotropy can be controlled by the height of the pillars and is only observed for hydrophilic surfaces.…”
Section: Introductionsupporting
confidence: 61%
“…The asymmetric three-dimensional architecture of the reconfigured posts is able to induce a directional wetting anisotropy of the liquid droplets deposited on the surface, with a consequent directional dependence of the observed CA along the TCL. Such contact angle anisotropy can be interpreted as depending on the energy barriers that TCL encounters on moving from the center of the liquid drop toward the outer regions of the substrate. ,, In this framework, the directions of the sample parallel to the long axis of the asymmetric microstructures are characterized by smaller energy barriers to the liquid propagation, which results in these directions being more energetically favored rather than the orthogonal ones. As a consequence, the TCL is mainly elongated in the direction of the long axis of the reconfigured structures, as reported in Figure e, which shows the photograph of a sessile water droplet (with blue dye) deposited onto the reconfigured asymmetric pillar array reported in Figure f.…”
Section: Resultsmentioning
confidence: 99%
“…An aligned PET (hydrophobic)/CHI (hydrophilic) fibrous surface (see Figure a) can be easily obtained via electrospinning technique coupled with a high‐speed‐collection drum (see Figure S1a in the Supporting Information). The hydrophobic/hydrophilic property of microstructures on the surface has a large impact on the wetting behavior of droplets, thus the anisotropy of PET/CHI surface can be controlled by tailoring the PET/CHI composition (see Figure S2 in the Supporting Information). As shown in Figure b, compared with a spherical shape (left, hydrophobic) on a pure PET fibrous surface, the ink droplet deforms to a stick‐like shape (middle, strong anisotropy with a length/width ratio ( L / W ) of ≈6.6) when PET/CHI is around 10/2.…”
mentioning
confidence: 99%